Kesesuaian Penanganan Ikan di Kapal pole and line - Dheni Rossarie; Yudhomenggolo Sastro Darmanto; Fronthea Swastawati (Jurnal Airaha, 2019)
Fish is a important sea catch, in addition to being the main source of protein, it is also the main livelihood for the fishermen. The handling of fish on board includes all actions starting from the initial to the final stage of storage. The decreasing quality and the high post-harvest damage are mostly affected by the fishing method, bad handling, the length of supply chain and the unavailability of handling facility. The government has put a high attention on the quality assurance of the fishery products by appointing the Decree of the Minister of Maritime and Fisheries Affairs Number 52A/Kepmen-KP/2013 on the Requirements for Quality Assurance and Security of Fishery Products.This research was conducted in the pier of PT Citra Raja Ampat Canning in Sorong City, the dock of pole and line ship. The method used in this research was the descriptive method and survey. The sampling method was using the purposive sampling. The result showed the suitability of the handling of skipjack in pole and line ship with the policy of quality management arranged in Ministrial Decree (KEPMEN-KP 52A/2013) from the element including the facility, equipment, handling method on the ship, and the role of the crew, in the ship 1, ship 2 and ship 3 was 61%, so it can be concluded that the handling on the pole and line ship was less than the standard.